THE FAMILY PLANNING PROGRAM ACCEPTORS’ ATTITUDE AND BEHAVIOR TO OVERCOME THE SIDE EFFECTS OF CONTRACEPTIONS - Sukmawati .; Lilis Mamuroh; Furkon Nurhakim; Tetti Solehati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
The contraceptive injection is one of the most widely used contraceptives by family planning acceptors in Garut Regency, especially in the Bayongbong Village. Side effects of the contraceptive injection include: amenorrhea, galactorrhea, bleeding, spotting, headache, lower abdominal pain, depression, hirsutism, hypertension, jaundice, decreased libido, nausea, dizziness, anxiety, thrombophlebitis, and weight gain and loss. The side effects of the contraceptive injection, if not addressed, would cause a drop out of acceptors of the family planning program. The attitudes and actions of family planning acceptors are one of the factors that influence the decision of the acceptors to continue to become the contraceptive injection acceptors or drop out. The purpose of this study was to determine the attitudes and actions of 3-month the contraceptive injection acceptors in overcoming side effects in the Bayongbong Village, Garut. The research method was descriptive, the sample of research was 72 people selected by random sampling technique. The analysis used was univariate. The results showed that 27 respondents (37.5%) had an unsupportive attitude and 45 people (62.5%) had a supportive attitude. While the actions of 32 people (44.4%) had good actions and 40 people (55.6%) had less action in overcoming the effects of 3 months injection of the family planning program. The side effects of the 3-month injection contraception device are one of the factors that can influence the decision to continue using contraception or not. Most respondents had non-supportive attitudes and fewer actions in overcoming side effects.Keywords: Side effect, injectable contraception, attitude, behavior